Теоретические и клинические исследования в нейроиммунологии - Stolyarov, I. D.; Petrov, A. M.; Ivashkova, E. V.; Votintseva, M. V.; Nikiforova, I. G. (Патогенез, 2023)
Доклад на конференции "Нейроиммунопатология".